How rude! : the teenagers' guide to good manners, proper behavior, and not grossing people out - Packer, Alex J.; Espeland, Pamela, 1951- (Minneapolis, MN : Free Spirit Pub., 1997)
A humorous but practical guide to good manners and social skills, discussing such areas as family life, behavior in public, manners in school, eating, and clothes.
Includes bibliographical references (p. 449-450) and index.
Keywords: Etiquette for children and teenagers; Etiquette